Current issues in Colorectal Cancer - Marijata Marijata (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Three issues about colorectal cancer are now blooming among surgeons and oncologists. The first issue is trend the younger the age of the patients suffering from colorectal cancer. The second is the younger the age of the patients the higher malignant of the cancer. The third issue is the delay of the management of colorectal cancer.Methods: A retrospective study on the colorectal cancer patients who were managed in Patmasuri Surgery Hospital, Yogyakarta, during a 10-year period (1989 - 1998).Results: The first and second issues were not proved, but the third issue was proved. The cause of delay came from the patient and the physician in establishing the diagnosis and in considering the operative procedure.Key words : colorectal cancer - younger age - higher malignant